Effectiveness of argument-driven inquiry (ADI) learning model on students' creative thinking skill: Environmental pollution - Inas Nuha Afifa; Neni Hasnunidah; Dina Maulina (Biosfer: Jurnal Pendidikan Biologi, 2021)
ADI learning model supports the syntax of the learning process through investigative activities of environmental pollution problems and their impact on the ecosystem. The model implements practicum to challenge students' creativity in presenting the results of practicum through students' arguments. The purpose of this study was to analyze the influence of the ADI learning model and evaluate the students' creative thinking skills. This was a quasi-experiment study with a pretest-posttest non-equivalent control group design. The sample was taken with cluster random sampling technique, 42 students were divided into 2 classes in 7th junior high school at Global Madani School, Bandar Lampung. Results were analyzed using covariance analysis and the effect size was measured by the partial eta-squared value. Aspects of creative thinking skills that were measured: fluency, flexibility, originality, elaboration, and metaphorical thinking. The result shows the application of the ADI learning model had a significant effect in improving students' creative thinking skills with a significance value of 0.013 (sig.<0.05). The effect of implementing the ADI learning model had high effectiveness in improving the students' creative thinking skills with a partial eta squared value of 0.147 which was categorized as large (sig ≥ 0.14). Therefore, the ADI learning model affects improving students 'creative thinking and had an impact on high effectiveness in improving students' creative thinking. Finally, the learning model is recommended for Biology teachers to increase students' creative thinking skills effectively.